A Parliament of Novels: the Politics of Scottish Fiction 1979-1999 - David Leishman (Revue Française de Civilisation Britannique)
The resurgence of Scottish literature at the end of the twentieth century took place in a troubled period of Scotland’s political and economic history, following 1979’s failed devolution referendum. The question raised here is that of the interaction between these two phenomena. The literature of the nineteen eighties and nineties is notably marked by its awareness of the issues underlying the representation of the working class and by its grounding in the socio-political context of the day.